Membangun Pondasi Bangsa Di Ruang Kelas Tetapi Juga Menyentuh Emosi Anak - Reza Amalia; Mirna Mirna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Education plays a strategic role in developing the quality of human resources while also serving as the primary means of shaping the character of a nation. However, educational practices in schools often remain focused on academic achievement and pay insufficient attention to the emotional development of students. In fact, healthy emotional development is an essential factor that influences learning success, social development, and children's character formation. This article aims to examine the importance of education that not only emphasizes the acquisition of knowledge but also touches children's emotions through humanistic and meaningful learning. This study employs a library research method by analyzing various books, scientific journals, and relevant documents related to character education, emotional intelligence, and humanistic learning. The findings of the study indicate that a classroom environment capable of meeting students' emotional needs can enhance learning motivation, self-confidence, social skills, and the development of positive character. Teachers play a central role in creating a safe, supportive, and empathetic learning environment through positive communication, respect for individual differences, and the provision of emotional support to students. Education that nurtures children's emotions helps develop a generation that is not only intellectually competent but also emotionally and socially mature. Therefore, sustainable nation-building should begin in the classroom by fostering an educational environment that develops both students' minds and hearts.